2017
DOI: 10.20944/preprints201712.0186.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Growth Hormone (GH) and Cardiovascular system

Abstract: This review describes the positive effects of growth hormone on the cardiovascular 13 system. We analyze why the vascular endothelium is a real internal secretion gland, whose 14 inflammation is the first step for developing atherosclerosis, as well as the mechanisms by which 15GH acts on the vascular endothelium improving its dysfunction. We also report how GH acts on 16 coronary arterial disease and heart failure, and on peripheral arterial disease inducing the 17 generation of new collateral vessels able to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…Furthermore, the caspase cascade is blocked and apoptotic rate is decreased. GH alleviates OS-induced apoptosis in some types of cells by activating the PI3K/Akt signal pathway [9][10][11]. We also found the same effects in the GCs of patients with PCOS.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Furthermore, the caspase cascade is blocked and apoptotic rate is decreased. GH alleviates OS-induced apoptosis in some types of cells by activating the PI3K/Akt signal pathway [9][10][11]. We also found the same effects in the GCs of patients with PCOS.…”
Section: Discussionsupporting
confidence: 77%
“…GH functions as an antioxidant in some types of cells, including oocytes, vascular endothelium, cardiomyocytes, and neural and skeletal muscle cells [9][10][11][12]34]. In this study, we found that in patients with PCOS, GH apparently decreased ROS production by > 50%, and signi cantly increased MMP and lowered the early and late apoptotic rates.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Another possibility for explaining the findings we observed is that GH has produced an increase in brain flow in the patient, allowing greater uptake of FDG. Recently, we described that GH induces an important reparative effect on the endothelial dysfunction that appears after atherogenic stimuli, such as hypercholesterolemia [37]; moreover, the hormone is a mitochondrial protector [38][39], and atherogenesis is related to oxidative stress. Therefore, since the patient we treated had high levels of plasma cholesterol and triglycerides it is also possible that, despite the short time of treatment, GH may have contributed to improve the blood supply to the brain, facilitating the appearance of the changes here described (both in terms of PET-SCAN images and cognitive tests).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that insulin resistance predisposes individuals to the development of obesity and dyslipidemia which are considered as the traditional risk factors. As insulin stimulates the production of NO which has both anti atherogenic and anti inflammatory effects, IR is considered as an endothelial dysfunction risk equivalent 18 . IR results in the down regulation of the antiatherogenic phosphatidylinositol-3-kinasemediated insulin receptor signaling pathway, and maintained activity of the pro atherogenic mitogenic activated protein kinase pathway.…”
Section: Tablementioning
confidence: 99%